(3LQGFe GdEgeGd ai eLGd GdhXjaI GdYGeI ai bGfhf GdYbhHGJ (B/ s - (3CMeO SYjO QGTO GdUQjOijs; (3CMeO YhV HdGds; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2011)
(3gOaJ GdOQGSI LQGFe GdEgeGd aj eLGd GdhXjaI GdYGeI aj bGfhf GdYbhHGJ GdJYQa Ydi GdCQcGf GdYGeI dLQGFe GdEgeGd aj COGA GdhXjaI GdYGeI (B: (3h GdJYQa Ydi JWHjbGJ LQGFe GdEgeGd aj COGA GdhXjaI GdYGeI(B: (3h GdJYQa Ydi eaghe GdehXa GdYGe aj cd ef GdbGfhf GdLfGFj h GdbGfhf GdEOGQj (B: (3h GdJYQa Ydi eaghe GdehXa GdYGe aj cd ef aQfSG h eUQ h GdEeGQGJ (B: (3h cPdc GdJYQa Ydi eaghe GdehXa GdYGe aj fWGb GdMeGjI GdELQGFjI(B. (3h GSJNOe GdHGMK GdefgL GdJMdjdi GdebGQf(B. (3GdCQcGf GdYGeI dLQjeI GdEgeGd aj COGA GdhXjaI GdYGeI(B: (3h JWHjbGJ LQGFe EgeGd GdehXa GdYGes
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2011s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B354-378s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdhXjaI GdYGeIs; (3LQGFe GdEgeGds; (3bGfhf GdYbhHGJs; (3GdehXa GdYGes; (3EgeGd GdMQGSs; (3abOGf ChQGb GdMcheIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs